2023
DOI: 10.1242/jeb.245747
|View full text |Cite
|
Sign up to set email alerts
|

Evolving views of ionic, osmotic and acid–base regulation in aquatic animals

Abstract: The regulation of ionic, osmotic and acid–base (IOAB) conditions in biological fluids is among the most fundamental functions in all organisms; being surrounded by water uniquely shapes the IOAB regulatory strategies of water-breathing animals. Throughout its centennial history, Journal of Experimental Biology has established itself as a premier venue for publication of comparative, environmental and evolutionary studies on IOAB regulation. This Review provides a synopsis of IOAB regulation in aquatic animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 232 publications
0
3
0
Order By: Relevance
“…Despite over a century of investigation and many excellent reviews detailing ionic, osmotic, and acid-base regulation (IOA-B) in teleost fish (Claiborne and Heisler, 1984; Cameron, 1989; Claiborne et al, 2002; Evans et al, 2005; Marshall and Grosell, 2006; Tresguerres et al, 2023), only a handful of studies have investigated blood pH and acid-base response to environmental alkalosis (Wilkie and Wood, 1991; Hemming and Hanson, 1992; Wilkie et al, 1993; McGeer and Eddy, 1998; Scott et al, 2005; Mcgeer et al, 2011). When freshwater teleosts are exposed to high pH conditions, there is an immediate increase in blood pH (pH e ) (Wilkie and Wood, 1991; Wilkie et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Despite over a century of investigation and many excellent reviews detailing ionic, osmotic, and acid-base regulation (IOA-B) in teleost fish (Claiborne and Heisler, 1984; Cameron, 1989; Claiborne et al, 2002; Evans et al, 2005; Marshall and Grosell, 2006; Tresguerres et al, 2023), only a handful of studies have investigated blood pH and acid-base response to environmental alkalosis (Wilkie and Wood, 1991; Hemming and Hanson, 1992; Wilkie et al, 1993; McGeer and Eddy, 1998; Scott et al, 2005; Mcgeer et al, 2011). When freshwater teleosts are exposed to high pH conditions, there is an immediate increase in blood pH (pH e ) (Wilkie and Wood, 1991; Wilkie et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to NKA and NHE3, the V-type H + -ATPase (VHA) has been proposed to excrete H + to compensate a blood acidosis in marine fishes, as it is the case in freshwater fishes (Tresguerres et al, 2023). Although VHA mRNA abundance was upregulated in some cases during exposure to ERH, there was little correlation between VHA mRNA expression and protein abundance (Allmon and Esbaugh, 2017; Michael et al, 2016) and VHA was not observed in the apical membrane of gill cells (Allmon and Esbaugh, 2017), where it would be expected to be found should it play a role in H + excretion.…”
Section: Introductionmentioning
confidence: 99%
“…One is the archetypical NKA-rich ionocyte, which additionally expressed VHA throughout its cytoplasm. The other one has abundant VHA in its basolateral membrane, does not express detectable NKA, and its function is still unclear (Tresguerres et al, 2023). We also reported that these fish were able to fully regulate blood pH upon exposure to ERH (1,600 μatm p CO 2 , pH ∼7.5, for three days) and identified the physiological mechanism that links blood and endolymph acid-base regulation with otolith overgrowth (Kwan and Tresguerres, 2022).…”
Section: Introductionmentioning
confidence: 99%